Kinematic calibration of a lightweight manipulator for medical applications - Arent, Krzysztof; Kurnicki, Adam; Portasiak, Piotr; Stańczyk, Bartłomiej (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The paper presents a kinematics calibration procedure for a lightweight manipulator designed for medical applications. They comprise improving the dexterity of a dysfunctional arm of a handicapped patient in an electric wheelchair as well as supporting biopsies and surgeries. Consequently, there are several manipulator distinguishing features of the manipulator design that are relevant to kinematics calibration. In particular, these are: a small area in the workspace within which the end-effector operates, affordability for non-commercial users, a delicate, dexterous design. In this context we propose a specialized procedure that features a low cost calibration tool enabling the end-effector to reach the correct positions for data acquisition. The key parameters of the calibration tool were obtained by applying two techniques of numerical analysis, workspace clustering and arbitrary choice, and subsequent experimental verification. The procedure exploits classical results concerning the kinematics calibration and is empirically verified by comprehensive simulation and experimental studies.